The Impact of Global Supply Chain Disruptions on Business Resilience: Lessons from the COVID-19 Pandemic (Universitas Kristen Indonesia Toraja, 2023)
The COVID-19 pandemic exposed vulnerabilities in global supply chains, significantly affecting business operations. This paper examines the strategies companies used to adapt to these disruptions and improve resilience. It discusses diversification, digitalization, and risk management practices, with case studies from manufacturing, retail, and logistics sectors. The findings offer actionable insights for building more robust and adaptive supply chains.